Brain-derived programmed death-ligand 1 mediates immunosuppression post intracerebral hemorrhage. Issue 11 (November 2022) - Cheng, Nuo; Wang, Hong; Zou, Ming; Jin, Wei-Na; Shi, Fu-Dong; Shi, Kaibin
Immunosuppression commonly occurs after a stroke, which is believed to be associated with the increased risk of infectious comorbidities of stroke patients, while the mechanisms underlying post-stroke immunosuppression is yet to be elucidated. In the brains of intracerebral hemorrhage (ICH) patients and murine ICH models, we identified that neuron-derived programmed death-ligand 1 (PD-L1) is reduced in the perihematomal area, associating increased soluble PD-L1 level in the peripheral blood. ICH induced a significant decrease of T and natural killer (NK) cell numbers in the periphery with an upregulation of programed death-1 (PD-1) in these cells. Blocking PD-1 pathway with an anti-PD1 monoclonal antibody prevented the T and NK cell compartment contraction and spleen atrophy post-ICH, with reduced pulmonary bacterial burden and improved neurological outcome. Thus, we here identified that brain-derived PD-L1 as a new mechanism driving post-stroke immunosuppression, and anti-PD1 treatment could be potentially developed to reducing the risk of post-stroke infections.